Diagnostic Accuracy of Methods Used to Detect Cracked Teeth - Kindaro, Veronica; Molland, Huon; Shirbegi, Sara; Renner, Paul; Krishnan, Unni (Clinical and experimental dental research, 2025)
ABSTRACT Objectives Cracked tooth diagnosis is challenging due to the unknown diagnostic accuracy of tools, resulting in misdiagnosis and suboptimal treatment outcomes. The primary objective of this study was to determine the diagnostic accuracy of four commonly used visual tests in diagnosing cracked teeth based on clinical appearance, independent of patient symptoms. The secondary objective was to assess if clinical experience influences the ability to accurately identify the presence of a crack. The tertiary objective was to assess the ability of the index tests to accurately determine the location of the crack. Material and Methods The test sample included 30 teeth extracted due to a suspected crack. Index tests included macrophotography, surgical microscope, transillumination, and DIAGNOcam. Microcomputed tomography (micro‐CT) served as the gold standard. Four examiners of varying experience assessed images of each tooth paired with each index test. The examiner's findings were compared against micro‐CT to determine the diagnostic accuracy of index tests. The relationship between clinical experience and diagnostic accuracy was explored. Results Transillumination demonstrated the highest accuracy (65.3%) and sensitivity (68.8%) for diagnosing cracks. Macrophotography and high‐magnification microscope had the highest specificity of 92.9%. Positive predictive value (PPV) was greatest with high‐magnification microscope (96.7%). The low‐magnification microscope demonstrated the lowest accuracy (52.2%). Intra‐rater reliability was moderate to substantial, and inter‐rater reliability was fair. Experienced dentists were more accurate in detecting cracked teeth. Conclusions Visual diagnostic methods cannot definitively diagnose cracks. Further studies are required to explore the impact of a combination of tools in diagnosing cracked teeth.